2013
DOI: 10.1002/14651858.cd003774.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral medications for preventing cytomegalovirus disease in solid organ transplant recipients

Abstract: Prophylaxis with antiviral medications reduces CMV disease and CMV-associated mortality in solid organ transplant recipients. These data suggest that antiviral prophylaxis should be used routinely in CMV positive recipients and in CMV negative recipients of CMV positive organ transplants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 138 publications
1
63
0
6
Order By: Relevance
“…Acyclovir and valacyclovir are also used to prevent CMV, although both have significantly reduced anti-CMV activity and are not recommended as first-line agents in recent guidelines (1-4), but are effectively used to prevent other human herpesvirus infections, including varicella, and as such have an important role in antiviral prophylaxis for CMV D−/R− SOT recipients. In early work on CMV prevention, acyclovir was determined to be inferior to oral ganciclovir (30), although at lower doses than others have used. Meta-analysis of direct comparison studies demonstrated that ganciclovir was more effective than acyclovir in preventing CMV disease (7 studies; RR 0.37, 95% CI 0.23-0.60) (31).…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%
“…Acyclovir and valacyclovir are also used to prevent CMV, although both have significantly reduced anti-CMV activity and are not recommended as first-line agents in recent guidelines (1-4), but are effectively used to prevent other human herpesvirus infections, including varicella, and as such have an important role in antiviral prophylaxis for CMV D−/R− SOT recipients. In early work on CMV prevention, acyclovir was determined to be inferior to oral ganciclovir (30), although at lower doses than others have used. Meta-analysis of direct comparison studies demonstrated that ganciclovir was more effective than acyclovir in preventing CMV disease (7 studies; RR 0.37, 95% CI 0.23-0.60) (31).…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%
“…31 Most of our kidney transplant recipients and their donors were seropositive, which is comparable with other studies. 10,12,31 Immunosuppression, leukopenia attacks, and rejection episodes Intensive immunosuppression is one of the main precipitating factors for CMV disease. 5,6 Half of our patients received thymoglobulin (Table 1), which has a severe bone marrow suppressive effect.…”
Section: Demographic Featuresmentioning
confidence: 99%
“…1 At our center, most kidney transplant recipients are at moderate risk for CMV infection and they receive universal prophylaxis due to its ease of administration, effectiveness, and prophylaxis against other viruses and possibly other bacterial and protozoan infections. [6][7][8][9][10][11][12] Valganciclovir is a valine ester prodrug of ganciclovir that was developed to overcome the limitations of oral and intravenous ganciclovir. [10][11][12] A single daily 900-mg oral dose provides comparable plasma ganciclovir exposures to those achieved with 5 mg/kg intravenous ganciclovir.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations